Regio- and stereoselective oxidation of unactivated C–H bonds with Rhodococcus rhodochrous - O’Reilly, Elaine; Aitken, Suzanne J.; Grogan, Gideon; Kelly, Paul P.; Turner, Nicholas J.; Flitsch, Sabine L. (Beilstein Journal of Organic Chemistry, 2012)
The ability of Rhodococcus rhodochrous (NCIMB 9703) to catalyse the regio- and stereoselective hydroxylation of a range of benzyloxy-substituted heterocycles has been investigated. Incubation of 2-benzyloxytetrahydropyrans with resting cell suspensions of the organism yielded predominantly a mixture of 5-hydroxylated isomers in combined yields of up to 40%. Exposure of the corresponding 2-benzyloxytetrahydrofuran derivatives to the cell suspensions gave predominantly the 4-hydroxylated isomers in yields of up to 26%. Most interestingly, 2-(4-nitrobenzyloxy)tetrahydrofuran and 2-(4-nitrobenzyloxy)tetrahydropyran were transformed in high yields to the 4-hydroxylated and 5-hydroxylated products, respectively.
Keywords: biocatalysis; cytochrome P450; hydroxylation; Rhodococcus rhodochrous; selective C–H activation

(untitled) - Chen, M. S.; White, M. C. (Science, 2007)

(untitled) - Weis, R.; Winkler, M.; Schittmayer, M.; Kambourakis, S.; Vink, M.; Rozzell, J. D.; Glieder, A. (Adv. Synth. Catal., 2009)

(untitled) - Schroer, K.; Kittelmann, M.; Lütz, S. (Biotechnol. Bioeng., 2010)

(untitled) - O'Reilly, E.; Köhler, V.; Flitsch, S. L.; Turner, N. J. (Chem. Commun., 2011)

(untitled) - Robin, A.; Köhler, V.; Jones, A.; Ali, A.; Kelly, P. P.; O’Reilly, E.; Turner, N. J.; Flitsch, S. L. (Beilstein J. Org. Chem., 2011)

(untitled) - Robin, A.; Roberts, G. A.; Kisch, J.; Sabbadin, F.; Grogan, G.; Bruce, N.; Turner, N. J.; Flitsch, S. L. (Chem. Commun., 2009)

(untitled) - Peters, M. W.; Meinhold, P.; Glieder, A.; Arnold, F. H. (J. Am. Chem. Soc., 2003)

(untitled) - Vail, R. B.; Homann, M. J.; Hanna, I.; Zaks, A. (J. Ind. Microbiol. Biotechnol., 2005)

(untitled) - Çelik, A.; Flitsch, S. L.; Turner, N. J. (Org. Biomol. Chem., 2005)

(untitled) - Flitsch, S. L.; Aitken, S. J.; Chow, C. S.-Y.; Grogan, G.; Staines, A. (Bioorg. Chem., 1999)

(untitled) - Grogan, G.; Roberts, G. A.; Parsons, S.; Turner, N. J.; Flitsch, S. L. (Appl. Microbiol. Biotechnol., 2002)

(untitled) - Larkin, M. J.; Kulakov, L. A.; Allen, C. C. R. (Curr. Opin. Biotechnol., 2005)

(untitled) - Jurtshuk, P.; Cardini, G. E.; Gibson, D. T. (Crit. Rev. Microbiol., 1971)

(untitled) - Cardini, G.; Jurtshuk, P. (J. Biol. Chem., 1968)

(untitled) - Chang, D.; Feiten, H.-J.; Engesser, K.-H.; van Beilen, J. B.; Witholt, B.; Li, Z. (Org. Lett., 2002)

(untitled) - Aitken, S. J.; Grogan, G.; Chow, C. S.-Y.; Turner, N. J.; Flitsch, S. L. (J. Chem. Soc., Perkin Trans. 1, 1998)

(untitled) - Holland, H. L.; Morris, T. A.; Nava, P. J.; Zabic, M. (Tetrahedron, 1999)

(untitled) - Floyd, N.; Munyeman, F.; Roberts, S. M.; Willetts, A. J. (J. Chem. Soc., Perkin Trans. 1, 1993)

(untitled) - Schwaneberg, U.; Schmidt-Dannert, C.; Schmitt, J.; Schmid, R. D. (Anal. Biochem., 1999)

(untitled) - Cirino, P. C.; Arnold, F. H. (Angew. Chem., Int. Ed., 2003)